A Criminological Perspective on Corruption as a Catalyst of Economic Breakdown: Socio-Legal Challenges in Indonesian Environmental Governance - Utari, Indah Sri; Preludio Ramada, Diandra; Alfarisi, Salman; Alias, Nizamuddin (Faculty of Law, Jambi University, 2026)
Corruption remains one of the most significant obstacles to sustainable environmental governance in resource-rich developing countries. While existing studies predominantly examine corruption as a governance failure or institutional deficiency, limited attention has been paid to its role as a criminogenic force that systematically generates economic breakdown. This study aims to analyze how structural corruption within Indonesia’s natural resource sector functions as a catalyst for economic decline through a socio-legal and criminological perspective. Employing a qualitative socio-legal approach, the research draws upon legal documents, government reports, anti-corruption records, and environmental governance cases in the mining, forestry, and plantation sectors. The findings demonstrate that corruption operates beyond individual acts of bribery and abuse of office; it functions as a structural mechanism that distorts resource allocation, weakens environmental law enforcement, facilitates regulatory capture, and accelerates ecological degradation. These processes generate substantial fiscal losses, undermine institutional legitimacy, discourage productive investment, and exacerbate socio-economic inequality. The study further reveals how state capture and patronage networks transform environmental governance into a system that privileges private economic interests over public welfare and sustainability objectives. The novelty of this research lies in its reconceptualization of corruption as a criminological driver of economic breakdown rather than merely a consequence of weak governance. By integrating green criminology, crimes of the powerful, and socio-legal analysis, this article develops a new analytical framework for understanding the relationship between corruption, environmental governance failure, and economic vulnerability. The findings contribute to criminological scholarship and provide policy insights for strengthening accountability and sustainable natural resource governance in Indonesia.